The investigation of health outcomes in the German National Cohort: the most relevant endpoints and their assessment - Ahrens, Wolfgang; Greiser, Karin H; Linseisen, Jakob; Pischon, Tobias; Pigeot, Iris (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2020)
The focus of the German National Cohort, the largest population-based cohort study in Germany to date, is the investigation of the most important widespread diseases, such as cardiovascular diseases, diabetes, cancer, neurological and psychiatric disorders, and frequent respiratory and infectious diseases. This cohort will answer questions on the development of these diseases and on the impact of genetic, environmental and lifestyle-related risk factors. Another focus is on the identification of early, subclinical markers of emerging diseases. To answer these questions, a comprehensive assessment of these health outcomes as well as of all potential determinants and precursors is mandatory.This paper describes the various health outcomes that are assessed in the German National Cohort, as well as the examination modules that are applied for deep phenotyping of study participants. Repeated collection of biosamples as well as functional measurements and application of modern imaging techniques at various time points allow for assessing the dynamics of physiological changes related to the individuals' health status. The prognostic value of these changes for disease development will be explored and translated to novel approaches for prevention and personalised medicine. Incident diseases are being assessed through self-reports by study participants and through record linkage with data from health insurances and cancer registries. Additional information about clinical diagnoses is obtained from the treating physicians to ensure the highest possible validity.